2010
DOI: 10.1016/j.powtec.2010.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and crystal structure of an equimolar Mg–Ti alloy processed by Simoloyer high-energy ball mill

Abstract: The solid solubility of 50-50 at.% Mg-Ti powder mixtures was achieved by means of high energy ball milling in a Simoloyer equipment. XRD 3Twins have nucleated on crystallite boundaries and grew inside the Ti-rich crystallites after short milling time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
(30 reference statements)
2
14
0
Order By: Relevance
“…1 also shows that significant peak broadening occurs due to straining through the HPT process, indicating the occurrence of lattice strain, dislocation generation and grain refinement. The formation of metastable phases in the Mg-Ti system due to HPT processing is consistent with the earlier reports on the formation of metastable phases in the Mg-Ti system by ball milling [19][20][21][22][23][24] as well as with earlier papers on facilitation of phase transformations by straining through HPT processing [32][33][34][35].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1 also shows that significant peak broadening occurs due to straining through the HPT process, indicating the occurrence of lattice strain, dislocation generation and grain refinement. The formation of metastable phases in the Mg-Ti system due to HPT processing is consistent with the earlier reports on the formation of metastable phases in the Mg-Ti system by ball milling [19][20][21][22][23][24] as well as with earlier papers on facilitation of phase transformations by straining through HPT processing [32][33][34][35].…”
Section: Resultssupporting
confidence: 92%
“…Borsa et al reported that a Mg-Ti alloy with the hcp structure is formed by co-sputtering of Mg and Ti in Ar atmosphere [18]. Asano et al [19][20][21], Rousselot et al [22], Calmak et al [23] and Maveja et al [24] reported that several metastable phases with bcc, fcc and hcp structures are formed in the Mg-Ti system by application of high-energy ball milling to Mg and Ti powders in Ar atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of the metastable Ti 50 Mg 50 alloy was recently successfully achieved by high-energy ball milling in a Simoloyer CM01-2lm (Zoz GmbH) in an argon atmosphere by the present authors [1]; and also by Rousselot et al using a shaker mixer mill Spex 8000 [2]. The above mentioned investigations demonstrated the extended solid solubility by ball milling of pure elemental titanium and magnesium metal powders with equiatomic composition with limits higher than previously reported in literature [3][4][5][6][7][8][9][10].…”
Section: Introductionsupporting
confidence: 68%
“…In an investigation of high energy milling of 50Mg-50Ti mixture, Maweja et al observed twinning in Ti-rich crystallites at intermediate milling time [68]. They attributed the twinning to the deformation of Ti particles.…”
Section: Mg-based Bccmentioning
confidence: 99%
“…But they also pointed out that in the Mg-Ti system it might also indicate a strain induced martensitic transformation of the metastable ω-FCC into BCC. The crystallite boundaries acted as preferential sites for the heterogeneous nucleation of the twins and for the formation of solid solution by release of the lattice strain energy [68].…”
Section: Mg-based Bccmentioning
confidence: 99%